Isolated inorganic phosphorus solubilizing bacteria from the rhizosphere of Coffea americana in Rioja – Peru - Soto Lovon, Julio Hipólito (2022)
Phosphorus is one of the macronutrients for the growth of vegetable crops, its low availability in the soil reduces the growth and yield of coffee crops, although the use of phosphorus fertilizers supplies the problem in the short term, in the long term they increase production costs and have a significant impact on the environment. The objective of this study was to evaluate and select microorganisms capable of solubilizing phosphate from the rhizosphere in coffee plantations (Rioja) to obtain a bank of microorganisms with biological fertilizer potential. A screening process of bacterial isolates, 15 codified bacteria from the rhizosphere of Coffea americana cultures, was carried out in SMRS1, NBRIP and Pikovskaya media to evaluate semi-quantitative tests of phosphate solubilization, having as main component tricalcium phosphate and phosphate monocalcium, obtaining values of Solubilization Index (IS) between 0.1 to values of 1.33. Subsequently, a quantitative measurement was made using an orthophosphate detection kit, obtaining values of up to 2,867 mg/L.